Praxeological and activity approach as a methodological basis of a competence oriented methodical training of the future Mathematics teacher - Акуленко, Ірина Анатоліївна (Pedagogy of Higher and Secondary Education, 2015)
Akulenko I. A. Praxeological and activity approach as a methodological basis of a competence oriented methodical training of the future Mathematics teacher. The article is focused on the praxeology and activity approach provisions that allow to formulate the basic principles of competence oriented methodical training of the future Mathematics teacher. Some expected results of its implementation were also identified.